1984
DOI: 10.1128/jb.157.2.545-551.1984
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characteristics of a gamma-glutamyl kinase involved in Escherichia coli proline biosynthesis

Abstract: y-Glutamyl kinase, the first enzyme of the proline biosynthetic pathway, was purified to homogeneity from an Escherichia coli strain resistant to the proline analog 3,4-dehydroproline. The enzyme had a native molecular weight of 236,000 and was apparently comprised of six identical 40,000-dalton subunits. Enzymatic activity of the protein was detectable only in assays containing highly purified-y-glutamyl phosphate reductase, the second enzyme of the proline pathway. Plots of-y-glutamyl kinase activity as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…A slight increase of Q-glutamyl-phosphate reductase speci¢c activity (from 5.1 to 8.0 nkat mg 31 ) was also observed, although no mutation in the proA gene was present. This was probably due to the occurrence of a physical interaction between the two enzymes, observed in other organisms [21], but the possibility of a positive downstream e¡ect of the proB mutation on proA transcription cannot be excluded.…”
Section: The Prob Mutation Causes An Enhancedmentioning
confidence: 99%
“…A slight increase of Q-glutamyl-phosphate reductase speci¢c activity (from 5.1 to 8.0 nkat mg 31 ) was also observed, although no mutation in the proA gene was present. This was probably due to the occurrence of a physical interaction between the two enzymes, observed in other organisms [21], but the possibility of a positive downstream e¡ect of the proB mutation on proA transcription cannot be excluded.…”
Section: The Prob Mutation Causes An Enhancedmentioning
confidence: 99%
“…The kinetic properties of the E. coli GK have been extensively characterized. The enzyme shows positive cooperativity with increasing glutamate concentration (Smith, Deutch & Rushlow, ; Seddon, Zhao & Meister, ): the concentration of glutamate that gives 50% activity ( S 0.5 ) in the absence of proline has been reported to be in the range of 16 mM (Seddon et al , ) to 82 mM (Pérez‐Arellano, Rubio & Cervera, ; Pérez‐Arellano et al , ). The latter researchers found that the S 0.5 for glutamate increased linearly with proline concentration, suggesting that glutamate and proline compete with each other for binding to the enzyme (Pérez‐Arellano et al , ).…”
Section: Pathway Through γ‐Glutamyl Phosphatementioning
confidence: 99%
“…We selected for a spontaneous mutation, mapping within the proB locus of pLC7-19, which conferred cellular resistance to 100 ig/ml of DHP. GK activity, from strains harboring plasmids which conferred DHP resistance, was considerably more resistant to the inhibitory effects of proline than the GK activity from wild-type strains (9). A 3.0 kb Pstl DNA fragment, isolated from the modified pLC7-19 plasmid, was identified as encoding both the affected proB locus and the wild-type proA locus (10).…”
Section: Construction and Screening Of Pgw7-proba Recombinantsmentioning
confidence: 99%